2018
DOI: 10.3892/etm.2018.6467
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hepatic blood inflow on liver ultrastructure and regeneration after extensive liver resection in rats with cirrhosis

Abstract: The aim of the present study was to investigate the effects of hepatic blood inflow on liver function, liver ultrastructure and the regeneration of future liver remnant (FLR) following major hepatectomy in rats with liver cirrhosis. A rat model of cirrhosis was established through intraperitoneal injection of carbon tetrachloride for 8 consecutive weeks. Extensive liver resection and different blood inflow models by portal vein (PV) and/or hepatic artery (HA) stenosis were conducted on the cirrhosis rats. Anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
3
4
0
Order By: Relevance
“…These findings were consistent with a previous animal study (Chow et al, 2012), the decrease of D * values resulted from the alteration in liver perfusion during the progression of liver fibrosis. Post-PH, the results clearly showed decreased liver D * values on day 1 and then gradual recovery in controls, but a continuous increase of liver D * values in the fibrosis group, findings consistent with previous studies (Harkness, 1952;Jin et al, 2018). The opposing changes in liver D * values between control and fibrotic livers in the early stage post-PH might result from the different microstructure and response of residual liver to PH.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings were consistent with a previous animal study (Chow et al, 2012), the decrease of D * values resulted from the alteration in liver perfusion during the progression of liver fibrosis. Post-PH, the results clearly showed decreased liver D * values on day 1 and then gradual recovery in controls, but a continuous increase of liver D * values in the fibrosis group, findings consistent with previous studies (Harkness, 1952;Jin et al, 2018). The opposing changes in liver D * values between control and fibrotic livers in the early stage post-PH might result from the different microstructure and response of residual liver to PH.…”
Section: Discussionsupporting
confidence: 90%
“…Harkness (1952) found that residual liver was much paler than control livers up to 48 h post-PH, and liver blood space decreased to a minimum at 48 h, followed by a gradual increase after a 67% hepatectomy in control livers. Jin et al (2018) found liver blood flow increased on day 1 and then decreased on day 5 after 45% PH by laser speckle contrast analysis in cirrhotic livers. However, those methods were invasive.…”
Section: Discussionmentioning
confidence: 84%
“…In humans, Doppler ultrasound has been the standard modality for this purpose; 10 yet it often yields incomplete or inaccurate hemodynamic data due to the limited size of acoustic windows, which can be compounded by overlying gas-filled bowels, 11 observer variability, 12 the difficulty of visualizing complex PV branches, 11 and the inability to measure three-dimensionally-variable flow using a 2D scanning technique. In small animals, flow meters, [13][14][15] lase specs, 16 and microspheres, 17,18 have been used to evaluate PV flow, but these modalities are too invasive to be used repeatedly, and the flow velocity data they provide is insufficiently detailed. Alternatively, several studies have used MRI to evaluate PV flow in humans and rodents, 19,20 concluding that MRI offers several advantages over the aforementioned modalities, including noninvasiveness, objectivity as opposed to examiner dependence, and a three-dimensional scanning area.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-five percent of the total hepatic flow is provided by the portal vein, which provides 50-70% of hepatic nutritional requirements [186]. Interplay between the portal and hepatic inflow has significant impact on hepatic regeneration [187]. This is especially true after orthotopic LT and even more so for LDLT.…”
Section: Impact Of Hepatic Flows In Liver Transplantmentioning
confidence: 99%